SomaticPIK3CAMutations in Sporadic Cerebral Cavernous Malformations - Matthieu Peyre; Danielle Miyagishima; Franck Bielle; Françoise Chapon; Michael C. Sierant; Quitterie Venot; Julie Lerond; Pauline Marijon; Samiya Abi-Jaoude; Tuan Le Van; Karim Labrèche; Richard S. Houlston; et al. (2021)
Cerebral cavernous malformations (CCMs) are common sporadic and inherited vascular malformations of the central nervous system. Although familial CCMs are linked to loss-of-function mutations in KRIT1 (CCM1), CCM2, or PDCD10 (CCM3), the genetic cause of sporadic CCMs, representing 80% of cases, remains incompletely understood.We developed two mouse models harboring mutations identified in human meningiomas with the use of the prostaglandin D2 synthase (PGDS) promoter. We performed targeted DNA sequencing of surgically resected CCMs from patients and confirmed our findings by droplet digital polymerase-chain-reaction analysis.We found that in mice expressing one of two common genetic drivers of meningioma - Pik3caH1047R or AKT1E17K - in PGDS-positive cells, a spectrum of typical CCMs develops (in 22% and 11% of the mice, respectively) instead of meningiomas, which prompted us to analyze tissue samples from sporadic CCMs from 88 patients. We detected somatic activating PIK3CA and AKT1 mutations in 39% and 1%, respectively, of lesion tissue from the patients. Only 10% of lesions harbored mutations in the CCM genes. We analyzed lesions induced by the activating mutations Pik3caH1074R and AKT1E17K in mice and identified the PGDS-expressing pericyte as the probable cell of origin.In tissue samples from sporadic CCMs, mutations in PIK3CA were represented to a greater extent than mutations in any other gene. The contribution of somatic mutations in the genes that cause familial CCMs was comparatively small. (Funded by the Fondation ARC pour la Recherche contre le Cancer and others.).